The inclusive management strategy : engineering culture change for employees with disabilities - Fawzy, Camelia M.; Shore, Brenda (Emerald Publishing Limited, 2019)
"Every person has the potential to contribute to an organization as long as they have access to the right opportunities and connections, yet it sometimes is all too obvious that the stigma associated with a person's disability can have a negative impact on their ability to develop healthy work relationships with peers and supervisors. This situation can only be remedied through effective change management, a systematic approach to designing, implementing, and measuring progress on unique culture-change goals." -- Provided by publisher